The Myth of Non-interference: Chinese Foreign Policy in Cambodia. Issue 1 (2nd January 2022) - Po, Sovinda; Sims, Kearrin
ABSTRACT: The discourse of "non-interference" features prominently in China's so-called "peaceful rise" and "win – win" approach to international diplomacy. This article contests Beijing's non-interference rhetoric through a case-study analysis of Cambodia. We make two core arguments: first, interference by foreign powers is not limited to actions that challenge a regime's leadership, but can also include the reinforcement of regimes that lack popular support. Second, Beijing's "non-interference" rhetoric is not demonstrated in the context of Cambodia, where it has repeatedly interfered to reinforce Prime Minister Hun Sen's leadership during times of political contestation. To make these arguments, the article offers a historical summary of Chinese interference in Cambodia followed by an analysis of the key domains in which Hun Sen's regime supports Chinese geostrategic interests. These are: support for Beijing's One China Policy and its Belt and Road Initiative; support for Beijing in negotiations with ASEAN; and support for Chinese economic interests. Collectively, we argue that these domains contribute to the advancement of China's "core national interest", and it is therefore a myth to suggest that China has not interfered in Cambodia's domestic politics.